IMPLEMENTASI STAD DAN SMART SPINNER UNTUK MENINGKATKAN MOTIVASI BELAJAR EKONOMI : Fenomena Siswa Kelas X di SMA Negeri 1 Rengel - Abdul Khafid Maulana; Dumiyati (ISTIQRA: Jurnal Hasil Penelitian, 2024)
The cooperative learning model is a student-centered learning model that demands more students to learn independently and is more active in discovering concepts and ideas with the help of a teacher who functions as a facilitator. The cooperative learning model used is student teams achievement divisions (STAD). This research is a type of classroom action research (PTK) to implement cooperative learning models of the STAD type with smart spinner media to increase student motivation in economics class XH SMA Negeri 1 Rengel with 38 students as research subjects, namely 17 boys and 21 girls. The research method used in this research is the Kurt Lewin model PTK method. The data collection techniques were interviews, observation, questionnaires, and documentation. They used teacher activity data analysis techniques to observe student motivation and responses. The results of research on teacher activity in cycle I was 50%, cycle II was 71%, and in cycle III it increased by 96.67%. Student learning motivation in cycle I was 55.50% in cycle II to 80.26% and in cycle III increased to 95.72%. Student responses in cycle I obtained a response of 85%, cycle II obtained a result of 91% and in cycle III a result of 97% (very large). From the results of this study, it can be concluded that the learning process using the STAD learning model with smart spinner media in economics subjects can increase the learning motivation of class XH students of SMA Negeri 1 Rengel